Fisherman shacks - Kjysten Drew:::Creator::::::::::::
Fisherman shacks before they were refurbished. These are now located along the 'chicken walk' on Irving Avenue between the Monterey Bay Coastal Bike Path and Cannery Row. Original is slide.